2015
DOI: 10.1088/0004-637x/807/2/145
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance Measurements in Plumes and Interplumes

Abstract: We present measurements of relative elemental abundances in plumes and interplumes. Plumes are bright, narrow structures in coronal holes that extend along open magnetic field lines far out into the corona. Previous work has found that in some coronal structures the abundances of elements with a low first ionization potential (FIP) <10 eV are enhanced relative to their photospheric abundances. This coronal-to-photospheric abundance ratio, commonly called the FIP bias, is typically 1 for elements with a high-FI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…That the FIP effect may depend on the time elements have been confined within a structure has been suggested by, e.g., Feldman and Widing (2003): this might possibly account for the different values obtained by different authors. A recent paper, Guennou et al (2015), further supports this hypothesis. These authors give values of relative element abundances in plumes and interplume regions, inferred from HINODE/EIS off-limb observations acquired in March 2007.…”
Section: Fip Effect In Plumes?mentioning
confidence: 65%
See 2 more Smart Citations
“…That the FIP effect may depend on the time elements have been confined within a structure has been suggested by, e.g., Feldman and Widing (2003): this might possibly account for the different values obtained by different authors. A recent paper, Guennou et al (2015), further supports this hypothesis. These authors give values of relative element abundances in plumes and interplume regions, inferred from HINODE/EIS off-limb observations acquired in March 2007.…”
Section: Fip Effect In Plumes?mentioning
confidence: 65%
“…Unfortunately, the data do not include lines from high-FIP elements and the FIP bias has been evaluated from the ratio of Fe and Si to S abundance, S being a moderate-FIP element (the sulphur FIP being ≈ 10.36 eV). Over 24-hour observations, one of the plume analyzed by Guennou et al (2015) revealed a decrease of the FIP bias, while other plumes (and interplume regions) have values independent of time. Guennou et al (2015) suggest this effect is related to the phase of the BP lifetime when plumes form above the associated BP, possibly plumes being representative of the abundances of the bright point.…”
Section: Fip Effect In Plumes?mentioning
confidence: 96%
See 1 more Smart Citation
“…Notes: (1) name given by NED (LCDCS clusters come from Gonzalez et al 2001), (2) right ascension in degrees (J2000.0), (3) declination in degrees (J2000.0), (4) redshift, (5) number of galaxies with redshifts in the cluster range, (6) useful XMM-Newton exposure time (in seconds), (7) temperature of the X-ray gas, (8) X-ray luminosity in the [0.5,8.0] keV band, (9) X-ray gas mass in the r 500 radius, (10) total mass in the r 500 radius, (11) subtructure inside the cluster (1 means yes, -1 means no, 0 means not detectable with data in hand). ** The position given for LCDCS 504 comes from Guennou et al (2013) where we determined the centre as the position of the cD, whereas the position given in parentheses was obtained from NED. *** The cluster MACS J1423.8+2404 did not have any XMM-Newton public data, but we collected Chandra data with enough depth to be able to subtract a β−model and search for substructures.…”
Section: Basic Parametersmentioning
confidence: 99%
“…Gemini/GMOS spectroscopy has a resolution of 7 Å/px (see Guennou et al 2013 for details). The targeted objects were brighter than I AB ∼ 24, and the reduction was made with the IRAF package and the Gemini/Gmos environment.…”
Section: Optical Data and Serna And Gerbal Analysismentioning
confidence: 99%